Neural tube defects 1974-94–down but not out. Issue 2 (September 1996) - Murphy, M; Seagroatt, V; Hey, K; O'Donnell, M; Godden, M; Jones, N; Botting, B
Abstract : AIMS: To describe accurately the total prevalence of neural tube defects (NTDs) in England and Wales over time, and to provide a benchmark up to 1994. METHODS: National data about NTDs reported as births or terminations are available from 1974-94, but reporting is incomplete. A local register of NTDs covering Oxfordshire/west Berkshire from 1965-94 was used to validate national data for the locality, using the method of capture and recapture, and hence to estimate incompleteness of reporting nationally. RESULTS: National underreporting is consistent at about two thirds of the true number of cases reaching at least the second trimester. The local register is much more complete, but time trends locally and nationally are similar. In England and Wales total prevalence declined from about 34 per 10000 live and stillbirths in 1974 to a plateau of just under 8 per 10000 in the 1990s. CONCLUSIONS: The decline in NTD prevalence is real and seems to have stopped. How this relates to changes in diet or the practice of vitamin supplementation is unknown, and the implications of the plateau are uncertain. OPCS figures of 500 NTDs annually in England and Wales represent about two thirds of the true number of cases.